Dinamika Lembaga Independen dalam Ketatanegaraan Indonesia - Sylvania Okta Aurelia; Alvi Septia Listyani; Aisyah Nabila Ramandhani; Syaefwanda Agita Saputri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This journal examines independent state institutions in Indonesian constitutionalism, which are an important element in maintaining the balance of power and the implementation of democracy. This journal focuses on the dynamics and concept of independent institutions in Indonesian state administration. Independent institutions, such as the Corruption Eradication Commission (KPK), the General Election Commission (KPU), and the Judicial Commission, are designed to operate freely from executive and legislative influence, maintain the integrity of government, and ensure justice. The purpose of this journal is to evaluate the effectiveness and efficiency of independent institutions in Indonesia in carrying out their duties and authorities. In an era of democracy and transparency, independent institutions are considered a means of checks and balances in government. These institutions ensure that the government acts by the rules and the public interest. With independent institutions, oversight of government policies and actions becomes more effective, reducing the risk of abuse of power or corruption. In addition, independent institutions play a role in increasing public accountability and trust in government, as well as providing objective recommendations and reports that can be used to improve government performance and ensure transparency in decision-making.